Diference in The Intensity of Emesis Before and After Acupressure at Point P6 in Pregnant Women During the First Trimester - Murni Handayani; Ni Nyoman Budiani; Ni Wayan Armini (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2025)
Emesis gravidarum, characterized by nausea and vomiting, significantly affects quality of life during early pregnancy. This study evaluated the effectiveness of acupressure at the P6 point in reducing the intensity of emesis in pregnant women in the first trimester. This study was conducted at the Independent Practice of Midwife Corriyati Yunus, Denpasar, with a pre-experimental design using a one group pretest-posttest approach. A total of 39 respondents were selected through purposive sampling. Data were collected using the PUQE-24 questionnaire and analyzed using the Wilcoxon test. The results showed a median emesis intensity of 8 before acupressure and 4 after, which showed a significant decrease (p-value = 0.000). These results confirm that acupressure at the P6 point is an effective and safe non-pharmacological therapy alternative to overcome nausea and vomiting during pregnancy. Further adoption of this technique is recommended to improve the welfare of pregnant women.